Clinicopathological Features of Pakistani Patients with Myelin Oligodendrocyte Glycoprotein Antibody Associated Disease (MOGAD) - Arshad, Muhammad Zain; Riaz, Muhammad Omair; Ahmad, Dawood; Hussain, Muhammad; Tanveer, Ayesha; Bibi, Maryam (Pakistan Armed Forces Medical Journal, 2024)
Objective: To characterize clinicopathological features of patients with Myelin Oligodendrocyte Glycoprotein Antibody Associated Disease in local population for early diagnosis and treatment. Study Design: Cross-sectional study. Place and Duration of Study: Department of Immunology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jun 2021 to Jan 2023. Methodology: Our study involved consecutive random sampling of 400 individuals presenting at Armed Forces Institute of Pathology for serum Anti Myelin Oligodendrocyte Glycoprotein antibody testing by indirect immunofluorescence. Commercial Anti Myelin Oligodendrocyte Glycoprotein Antibody Indirect Immunofluorescence Test Slides along with controls were used and immunofluorescence was observed using fluorescent microscope BA-310. Detailed data was collected on a predesigned proforma, and qualitative and quantitative variables were analysed using statistical software. Results: Eleven (2.75%) patients were positive for Anti Myelin Oligodendrocyte Glycoprotein antibodies with a male to female ratio of 1.6:1 (p =0.882). Mean age of diagnosis was 30.3±12 years. At time of diagnosis, all patients had 2 or more core clinical characteristics, of which, most prevalent was transverse myelitis, optic neuritis and headache/fever present in 4(80%) patients. The average diagnostic delay in our study was 20 months. Conclusions: By having a high index of suspicion for presenting core clinical characteristics of Myelin Oligodendrocyte Glycoprotein Antibody Associated Disease, clinicians may be able to diagnose and treat this rare ailment in a timely manner to decrease diagnostic delay and prevent associated morbidity and mortality.